Isolable Cu(I) Complexes of Extremely Electron-Poor, Completely Unreduced o-Quinone and "Di- o-Quinone" Ligands Stabilized through π-π Interactions in the Secondary Coordination Sphere - Albold, Uta; Hoyer, Carolin; Neuman, Nicolás I; Sobottka, Sebastian; Hazari, Arijit S; Lahiri, Goutam Kumar; Sarkar, Biprajit (Inorganic chemistry, 2019)
The copper-quinone interaction plays important roles in diverse fields such as biochemistry, catalysis, and optically/magnetically switchable materials. Despite this fact, the isolation and thorough characterization of copper(I)-quinone complexes remains a highly challenging task owing to their intrinsic instability. We herein present systems where the stability imparted by the extended π-system of a pyrene ring is used to synthesize, isolate, and crystallographically characterize the first example of a dinuclear metal complex that is bridged by a completely unreduced "di- o-quinone"-type ligand. Additionally, we present the monocopper counterpart with the o-quinone-pyrene type of ligand. The copper complexes are redox-rich and display intriguing electrochemical, optical, and electron paramagnetic resonance (EPR) spectroscopic properties. The line-rich EPR spectra of the one-electron reduced copper(I) complexes were simulated and analyzed via density functional theory calculations. The results presented here establish π-π stacking as a viable alternative to stabilize otherwise unstable redox-active compounds with possible consequences for sensing and redox catalysis.